Reducing global environmental inequality: Determining regional quotas for environmental burdens through systems optimisation. (10th October 2020) - Pozo, C.; Galán-Martín, A.; Cortés-Borda, D.; Sales-Pardo, M.; Azapagic, A.; Guimerà, R.; Guillén-Gosálbez, G.
Abstract: Reducing inequality is essential for sustainable development, yet our understanding of its many dimensions and driving forces is still limited. Here we study the global distribution of 25 environmental burdens encompassing natural resources (water, materials and land use) and air emissions, all related to activities underpinning human welfare. We find large disparities in inequality levels across burdens and a general, yet slow, decline in inequality in the period 1995–2009, explained mostly by the faster economic growth of emerging economies. Acknowledging that allocation issues may hamper greater equality, we propose a framework for an optimal allocation of quotas for environmental burdens respecting a maximum allowable inequality limit while ensuring a safe operation within the Earth's ecological capacity. Our results shed light on the global distribution of environmental burdens and provide a roadmap for achieving a greater environmental equality using systems optimisation. It is hoped that this work will trigger further discussion on the need to address environmental inequality, currently missing in the Sustainable Development Goals, and open up new research avenues on the use of whole-systems approaches in solving global sustainability problems. Highlights: Significant disparities are observed in global inequality in environmental burdens. Inequality is declining in 22 of the 25 burdens considered, but at a slow pace. A roadmap towards environmental equality based on systems optimisation is proposed. This can be used for policies to reduce inequality within the planetary boundaries.